Mitochondrial complex II and reactive oxygen species in disease and therapy - Katerina Hadrava Vanova; Michal Kraus; Jiri Neuzil; Jakub Rohlena (Taylor & Francis Group, 2020)
Increasing evidence points to the respiratory Complex II (CII) as a source and modulator of reactive oxygen species (ROS). Both functional loss of CII as well as its pharmacological inhibition can lead to ROS generation in cells, with a relevant impact on the development of pathophysiological conditions, i.e. cancer and neurodegenerative diseases. While the basic framework of CII involvement in ROS production has been defined, the fine details still await clarification. It is important to resolve these aspects to fully understand the role of CII in pathology and to explore its therapeutic potential in cancer and other diseases.